Viability and germination of seeds of Puya raimondii Harms (Bromeliaceae) - Vadillo, Giovana (2004)
Puya raimondii Harms is an endemic species of the highlands of Peru and Bolivia between 3200 to 4800 m of altitude with noticeable great size and beauty. It is considered threatened species; therefore it is urgent to know the factors that affect its viability and germination of their seeds; aspects focused work presently. The seeds were collected in 1999 and 2000 in Huashta Cruz (Pueblo Libre, Ancash, Peru) and they classified as lots (considering their origin and appearance). They were determined their moisture content and the viability (quality). By means of germination tests, it was evaluated in 5 lots the effect of the light and temperature. The seeds presented different viability which depended on the conditions they were exposed in situ and that it is correlated inversely with its content of humidity, affecting its appearance inclusive. The seeds exposed to the light presented high percentage of germination (positive photoblastics, require light to germinate). Temperatures higher than 21°C had a negative effect in the percentage of germination and germination speed index.